Predicting Students’ Learning Perceptions through Deep Learning Pedagogy within a Transformative Curriculum: Evidence from Indonesian Islamic Higher Education - Pahrudin, Agus; Sugiharta, Iip; Arifin, Zainal (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – Islamic higher education institutions increasingly promote transformative and holistic curricular goals; however, empirical modeling that explains how deep learning pedagogy operates within Islamic epistemological commitments and predicts students’ learning perceptions remains limited. This study examines how Meaningful Learning, Mindful Learning, and Joyful Learning, as dimensions of Deep Learning pedagogy, predict students’ learning perceptions within a transformative curriculum framework in Indonesian Islamic higher education. Design/methods/approach – An exploratory sequential mixed-methods design was employed. Semi-structured interviews were conducted with 27 academic leaders and lecturers from three Indonesian Islamic universities. Based on qualitative theme-to-item translation, a questionnaire was developed and administered to 300 undergraduates using a cross-sectional survey. The instrument demonstrated good to excellent reliability (α = 0.84–0.86; overall α = 0.94). Multiple linear regression was applied. Findings – Qualitative findings indicate that Deep Learning operates as an integrated pedagogical process linking contextual relevance, reflective engagement, and emotional involvement within a value-oriented instructional ecology. Quantitative results show that Meaningful Learning, Mindful Learning, and Joyful Learning jointly explain 71.7% of the variance in students’ learning perceptions (R² = 0.717). Meaningful Learning and Joyful Learning emerge as the strongest predictors (β = 0.39), while Mindful Learning contributes positively with a smaller magnitude (β = 0.17). Research implications/limitations – The findings suggest that effective transformative curriculum implementation in PTKI/PTAIS contexts requires intentional integration of cognitive relevance, reflective awareness, and emotional engagement within curriculum design, lecturer development, and institutional support systems. Limitations include the cross-sectional design, reliance on self-report measures, and limited institutional scope. Originality/value – This study contributes theoretically by recontextualizing Deep Learning constructs within an Islamic epistemological framework, particularly through a tawhidic integration of cognitive, reflective, and affective dimensions. By empirically modeling students’ learning perceptions as an integrative indicator of transformative learning in Indonesian Islamic higher education, this study extends mainstream Deep Learning theory beyond its predominantly Western cognitive-reflective orientation toward a value-embedded pedagogical paradigm.